Touring in heterotopia: Travel, sovereignty, and exceptional spaces in Taiwan and China. Issue 1 (2nd January 2017) - Rowen, Ian
Abstract : This article uses the case of Chinese tourism to Taiwan to theorize the mutual constitution of tourism mobilities and exceptional spaces of sovereignty. Human flows between China and Taiwan have proliferated despite incompatible sovereign claims. Since 2008, China has sent millions of tourists across the Taiwan Strait even as it points over a thousand missiles in the same direction. Taiwan, itself a "de facto state" and therefore an "exceptional space" in the normative world order of sovereign nation-states, is partly defined by its relations with China. This relationship is being refashioned through cross-Strait tourism. Based on analysis of border-crossing regulations and ethnographies of tourist spaces, particularly at airports and protest sites, conducted between 2012 and 2015, this article argues that tourism mobilities are not only the effect but also the cause of transformations in the performance of sovereignty and territoriality. In other words, such mobilities not only articulate within exceptional spaces, but they can produce and reconfigure such spaces as well.